Determining Pre-Service Teachers’ Astronomy-Related Self-Efficacy Belief Levels - Ebru Ezberci Cevik; Oktay Bektaş (Center for Educational Policy Studies Journal)
This study aims to reveal the astronomy-related self-efficacy beliefs of pre-service teachers studying science education, primary school education, and social studies education programmes. The study is conducted using the survey design, a quantitative research method. The study sample consists of 322 pre-service teachers in their third or fourth year of a science education, primary school education, or social studies education programme at a university in Turkey’s Central Anatolia Region during the 2016 fall semester. The Astronomy Teaching Self-Efficacy Belief Scale developed by Güneş was used as the data collection tool. SPSS 22 was used to analyse the data, and the analyses benefited from descriptive and inferential statistics. Based on the findings, the pre-service teachers’ total scores for astronomy self-efficacy showed no significant difference in terms of certain variables (i.e., gender, age, year, and having taken a previous astronomy course). However, significant differences were found regarding self-efficacy scores in terms of the programme and having taken part in astronomy and sky-gazing activity. Concerning the obtained results, the following suggestions can be made: pre-service teachers should be actively involved during the astronomy course, and their classroom management experiences should be promoted to improve their astronomy self-efficacy belief levels.